Effect of the phosphorus-solubilizing bacterium Enterobacter ludwigii on barley growth promotion. - Zaballa, José Ignacio (2020)
Phosphorus (P) is essential for plant growth and development but is often a limiting nutrient in soils. Thus, Pi acquisition from the soil by plant roots is a subject of considerable interest in agriculture. One ecological alternative is the use of P-solubilizing bacteria, which make P available to plants through different mechanisms. Thus, the aim of the present study was to investigate the role of the P-solubilizing bacterium Enterobacter ludwigii in the growth promotion and P content of Hordeum vulgare (barley) under field conditions. Plants were inoculated with E. ludwigii and then its growth promotion effects were compared with those of the reference strain Azospirillum brasilense. The effect of bacterial inoculation showed a beneficial effect on the dry weight, P assimilation and barley yield, especially in E. ludwigii-inoculated plants. The plant P content at 60 DAS was 38% to 56% higher in E. ludwigii -inoculated plants with respect to non-inoculated plants. The application of bacteria without fertilizer led to the same biological yield (3,795 kg/ha) and increase in one thousand seed weight as the maximum dose of chemical fertilizer applied, while the application of bacteria along with the intermediate fertilizer dose led to a significant increase in grain size (83% of plump grains larger than 2.75 mm wide, whereas 76% of the grains of the control plants reached that size). Endophyte populations of the inoculated bacteria were observed in plants growing under field conditions. The results demonstrated that the inoculation of with E. ludwigii is a promising option to increase P levels in plants and could be a technique for application in agricultural industry.